Registros contables de los beneficios de empleados de la empresa Dr. Agro del Cantón Montalvo, provincia de Los Ríos durante el periodo 2023. - Rumbea Ramos, Jomayra Beatriz (2024)
This case study focuses on employee benefit accounting records, an important aspect of financial management in modern organizations. Since employee benefits account for a large portion of operating costs, proper management and accounting are essential for financial transparency and strategic decision-making. Social benefit accounting records refer to journal entries that reflect the wage benefits that an employee must receive, in accordance with the regulations established in the labor code. However, the lack of accuracy in the base salary recorded in the general role negatively affects the calculation of these benefits, which in turn compromises the accuracy of the accounting records in the daily book. Non-compliance with regulations can influence accounting regulations and vary depending on the type of profit. In addition, financial budgets can be affected if the actual costs associated with social benefits are not considered, which can lead to penalties or fines during an audit, which assesses both financial transparency and regulatory compliance. As for the salary table, the base salary was $425.00 in 2022 and $450.00 in 2023.